Coordenadores iniciantes e experientes e as práticas de acolhimento, acompanhamento e indução : eu, eles e o espelho - Silva, Jéssica Lorrayne Ananias da (2021)
The present research is linked to the Post graduation Program in Education of the Social and Human Sciences Institute of the Universidade Federal de Mato Grosso, (PPGEdu/UFMT), in the research line called Teachers´ Education and Educational Public Policies. It is inserted in the research group InvestigAção, in which was linked till 2017, the Observatory of Education (OBEDUC). The investigation aimed at understanding how the performance of the beginner pedagogical coordinators (BPC) and experienced ones (EPC) happens in the work, regarding reception/ assistance and induction of the teachers in their career start (TS) during the first semester. To this end, the following investigation questions are presented: Is it possible to detect, in the SEMED/ROO education for the pedagogical coordinators, actions that lead to induction projects with beginners in the municipal schools? What do the beginners reveal about the assistance and education/induction in the first six critical months in their professional practice? How do the beginner teachers understand the processes of assistance, insertion and induction when developed by pedagogical coordinators beginners and experienced? The research is based on the qualitative approach. To participate in this investigation, two beginner pedagogical coordinators, two experienced ones and two beginner teachers were selected, those who actuate in the municipal schools in Rondonópolis, municipality of Mato Grosso. We adopt as procedure and instrument of data collection reflective interviewing and document analysis. As result of the research, the narrative reveals that both action of reception and assistance offered to the beginners come from, mainly, the pedagogical coordinators auto education and the interventions tend to be specific. Although it does not exist an institutionalized project that covers the teachers’ induction, the effort to put them into practice are being done. The investigation also indicated that the pedagogical coordinators need an assistance in their educational needs regarding the reception, assistance and induction to the beginners.